Risk assessment tool for software project in Malaysian public sector - Omar, Razita; Din, Jamilah (Medwell Journals, 2017)
Software products and services are designed and developed in software project that utilize large amount of resources. Risk assessment is an essential activity for software projects to achieve project’s objectives. Quality of risk assessment process could affect the quality of the delivered project or worst it will lead to a project failure. In Malaysian public sector, Information Communication and Technology (ICT) has been rapidly utilized as an enabler to modernize service delivery via multiple electronic channels. This study aims to identify the relevant criteria (variables) in risk assessment and to design and implement a risk assessment tool, specifically tailored to Malaysian Public Sector Software Project. The study were performed through exploratory research methodology focuses on qualitative risk assessment in risk management capacity. The focus group was employed to imply the public sector risk assessment variables for software project. An interview session and discussion with focus group were conducted to gather the requirements in order to achieve our aims. The outcome of this risk assessment tool is to produce risk report table consist of risk probability, risk impact and risk score. The risk assessment tool proposed is believe to be useful in speeding up the process and also to assist the decision making process in risk management area. As for future researches, we are planning to further our study on the complete process of risk management for software project in Malaysia public sector. Investigation of risk assessment should take the complete process of risk management into consideration of performing good risk management tool.